2013
DOI: 10.4236/epe.2013.58053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shape of the Absorber Surface on the Performance of Stepped Type Solar Still

Abstract: In this work, we have selected three number of stepped type solar stills of the same overall dimensions 620 mm (W) × 808 mm (L) but with different absorber surface areas due to the variation in the shape of the basin surface. The other design parameters like depth of water, thickness of glass cover, insulation thickness, type of condensing cover, absorbing material provided over the basin, and angle of inclination of the still were kept constant to study the effect of shape of the absorber surface over the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Improving the stepped solar still productivity by adding different heat storage materials on the absorber surface was studied experimentally by Gawande and Bhuyar [28] in Buldana, India. The enhanced stepped stills of [28] shown in Figure 13, were equipped one with square sponges and the other with circular fins, both were compared with simple stepped solar still of [10].…”
Section: Stepped Solar Stills' Basin Additions Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the stepped solar still productivity by adding different heat storage materials on the absorber surface was studied experimentally by Gawande and Bhuyar [28] in Buldana, India. The enhanced stepped stills of [28] shown in Figure 13, were equipped one with square sponges and the other with circular fins, both were compared with simple stepped solar still of [10].…”
Section: Stepped Solar Stills' Basin Additions Improvementsmentioning
confidence: 99%
“…Improving the stepped solar still productivity by adding different heat storage materials on the absorber surface was studied experimentally by Gawande and Bhuyar [28] in Buldana, India. The enhanced stepped stills of [28] shown in Figure 13, were equipped one with square sponges and the other with circular fins, both were compared with simple stepped solar still of [10]. Both the modified systems indicated that, the productivity was increased by about 25.5% and 33.6% for stepped stills with fins and sponges respectively, compared with the simple stepped one.…”
Section: Stepped Solar Stills' Basin Additions Improvementsmentioning
confidence: 99%
“…Assuming water vapor follows the ideal gas law, the following expression for evaporative heat flux was considered (Gawande and Bhuyar, 2013); q 00 e;wÀg ¼ h e;wÀg ðT w À T gi Þ (6)…”
Section: Effect Of Absorber Platementioning
confidence: 99%
“…(J.S. Gawande, et al, 2013) in their experiment used different absorbing materials in a single basin solar still of area 0.6 m2 with. Black color was painted in the basin surface with to increase the absorptivity of the solar still.…”
Section: Introductionmentioning
confidence: 99%